2020
DOI: 10.1029/2019jg005624
|View full text |Cite
|
Sign up to set email alerts
|

The Photochemical Reflectance Index (PRI) Captures the Ecohydrologic Sensitivity of a Semiarid Mixed Conifer Forest

Abstract: At the seasonal time scale, daily photochemical reflectance index (PRI) measurements track changes in photoprotective pigment pools as plants respond to seasonally variable environmental conditions. As such, remotely sensed PRI products present opportunities to study seasonal processes in evergreen conifer forests, where complex vegetation dynamics are difficult to capture due to small annual changes in chlorophyll content or leaf structure. Because PRI is tied explicitly to short-and long-term changes in phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 142 publications
(290 reference statements)
1
18
0
Order By: Relevance
“…in the afternoon of the hotter days) the response of NPQ saturated, indicating that the temporal kinetics of stomata and the light reactions can decouple during heatwave events (Meinzer et al ., 2017). The apparent link between NPQ and stomatal conductance, also suggested in previous research (Medrano et al ., 2002; van der Tol et al ., 2009) and exploited through RS with the PRI index (Suárez et al ., 2008; Yang et al ., 2020), needs to be further investigated. In particular, a process‐based understanding of the relationship between stomatal conductance, NPQ and SIF needs to be established to correctly use SIF as a proxy for transpiration.…”
Section: Discussionmentioning
confidence: 99%
“…in the afternoon of the hotter days) the response of NPQ saturated, indicating that the temporal kinetics of stomata and the light reactions can decouple during heatwave events (Meinzer et al ., 2017). The apparent link between NPQ and stomatal conductance, also suggested in previous research (Medrano et al ., 2002; van der Tol et al ., 2009) and exploited through RS with the PRI index (Suárez et al ., 2008; Yang et al ., 2020), needs to be further investigated. In particular, a process‐based understanding of the relationship between stomatal conductance, NPQ and SIF needs to be established to correctly use SIF as a proxy for transpiration.…”
Section: Discussionmentioning
confidence: 99%
“…Among the carotenoid‐sensitive indices, PRI was most successful in capturing changes in photochemical efficiency over short timescales and was thus selected over CCI for this study. Its potential as a proxy for monitoring drought stress has been amply investigated for Mediterranean vegetation, where summer drought represents the primary environmental constraint (Goerner, Reichstein, & Rambal, 2009 ; Hernández‐Clemente, Navarro‐Cerrillo, Suárez, Morales, & Zarco‐Tejada, 2011 ; Marino et al, 2014 ; Peguero‐Pina, Morales, Flexas, Gil‐Pelegrín, & Moya, 2008 ; Peñuelas, Munné‐Bosch, Llusià, & Filella, 2004 ; Stylinski, Gamon, & Oechel, 2002 ; Yang et al, 2020 ; Zarco‐Tejada, González‐Dugo, & Berni, 2012 ; Zhang, Preece, Filella, Farré‐Armengol, & Peñuelas, 2017 ). Among these are early studies by Zarco‐Tejada and colleagues, which demonstrate the ability of airborne PRI to track seasonal and diurnal changes in stem water potential, stomatal conductance and canopy to air temperature differences in Spanish tree orchard ecosystems under different irrigation regimes (e.g., Suárez et al, 2008 ; Suárez et al, 2010 ; Zarco‐Tejada et al, 2012 ; Zarco‐Tejada et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported similar results of foliar spectral traits in assessing plant attributes (productivity) in other semi-arid ecosystems. Vegetation indexes, such as NDVI, GI, and OSAVI, reflected information of leaf area index and chlorophyll content, and were often used in inversion of vegetation coverage and growth status (Li et al, 2009;Ferna et al, 2018;Yang et al, 2020). NDVI and OSAVI estimated green biomass and vegetative coverage in grass ecosystem (Ferna et al, 2018), while PRI estimates instant light use efficiency at leaf scale, which was used to track changes of photoprotective pigment pools and capture eco-hydrologic sensitivity of a mixed conifer forest (Yang et al, 2020).…”
Section: Linkage Between Foliar Spectral Traits and Plant Productivit...mentioning
confidence: 99%
“…Vegetation indexes, such as NDVI, GI, and OSAVI, reflected information of leaf area index and chlorophyll content, and were often used in inversion of vegetation coverage and growth status (Li et al, 2009;Ferna et al, 2018;Yang et al, 2020). NDVI and OSAVI estimated green biomass and vegetative coverage in grass ecosystem (Ferna et al, 2018), while PRI estimates instant light use efficiency at leaf scale, which was used to track changes of photoprotective pigment pools and capture eco-hydrologic sensitivity of a mixed conifer forest (Yang et al, 2020). Daily PRI measurements could be used to track changes of photoprotective pigment pools as plants respond to seasonal environment change.…”
Section: Linkage Between Foliar Spectral Traits and Plant Productivit...mentioning
confidence: 99%